Inguinal herniotomy in children with and without peri-operative chemoprophylaxis (Journal of Paediatric Surgeons of Bangladesh, 2023)
Purpose: The aim of the study is to find out any difference in the outcome regarding wound infection of inguinal herniotomy in children with and without peri-operative chemoprophylaxis.Patients and Methods: This prospective interventional comparative study was conducted in the department of Paediatric Surgery, Dhaka Medical College Hospital from July, 2014 to June, 2016. Children (1 month to 12 years) with inguinal hernia attended in out patient department were included and children with other varieties like irreducible, obstructed, strangulated and infected inguinal hernias were excluded from the study. Patients were divided in Group A (Patient with peri-operative chemoprophylaxis) and Group B (Patient without peri-operative chemoprophylaxis). Ethical clearance was taken from the ethical review committee (ERC) of Dhaka Medical College. Local rise of temperature, redness, swelling, serous discharge in post-operative wounds, cost effectiveness, hypersensitivity reaction were compared between study groups. Results: Total 100 patients were studied, 50 in each group. There was no significant difference between Group A and Group B regarding local rise of temperature (P =0.75), redness (P =0.75), swelling (P =0.75), serous discharge in wound (P =0.32) but highly significant (P ˂0.001) regarding cost of treatment in taka. There was no record of any hypersensitivity reaction during or following the treatment in any group.Conclusions: This study revealed that peri-operative chemoprophylaxis is not superior to peri-operative without chemoprophylaxis in regards to local rise of temperature, redness, swelling, serous discharge in wound. It is concluded that the peri-operative chemoprophylaxis may not be necessary in clean surgery like inguinal herniotomy in children.Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 33-38